Molecular docking of capsaicin and its derivatives as acetylcholinesterase (AChE) inhibitors in Alzheimer disease - Syah, Vicky Ardian; Geralda, Rifka; Sakti, Nickyta Salsabila Ira; Febriyanti, Kharisma; Bokshow, Rency Violita Vanden; Wulandari, Valentri; Hasanah, Siti Fadhilatul; Fadillah, Muhammad Zakki; Auli, Winni Nur; Saputro, Anjar Hermadi (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder predominantly affecting older adults, characterized by pathological processes that include excessive acetylcholinesterase (AChE) activity leading to depleted acetylcholine levels. Although synthetic AChE inhibitors such as donepezil are used therapeutically, their clinical application is often limited by adverse effects and high costs. Capsaicin, a bioactive compound derived from chili peppers, has exhibited neuroprotective properties—including cognitive enhancement and amyloid-β reduction—suggesting its potential as a natural alternative for AD treatment. This study investigated capsaicin and six structural derivatives as potential AChE inhibitors through in silico molecular docking simulations against the human AChE crystal structure (PDB: 4EY7), using donepezil as a reference ligand. The docking protocol was validated with a root-mean-square deviation (RMSD) value of 0.71 Å, confirming reproducibility and reliability. The calculated binding affinities of the evaluated compounds ranged from –6.13 to –11.60 kcal/mol. Among them, 2-Hydroxy-3-(octyloxy)phenyl-5-(acrylamido)methylbenzophenone (Compound 2) exhibited the strongest binding affinity (–11.60 kcal/mol), slightly exceeding that of donepezil (–11.45 kcal/mol). Compound 2 formed four hydrogen bonds within the active site and shared key interactions with residues Phe338 and Trp286, consistent with the binding mode of donepezil. These results suggest that Compound 2 may serve as a potent natural AChE inhibitor and warrant further investigation as a candidate for Alzheimer’s disease therapy.